The Effect of Grip Strength and Anticipation on Spin Serve Effectiveness in Junior Tennis Players - Ians Aprilo; Poppy Elisano Arfanda; M. Adam Mappaompo; Hasbi Asyhari; Muhammad Isnawan Syafir (Journal Physical Health Recreation (JPHR), 2025)
This study investigates the effect of racket grip strength and motion anticipation on the effectiveness of spin serves among junior tennis athletes in Makassar. Using a quantitative correlational design, 20 athletes aged 14–18 years participated. Grip strength was measured with a handgrip dynamometer, motion anticipation with a visual reaction test, and spin serve effectiveness through video analysis of accuracy, direction, and bounce. Multiple regression analysis (α = 0.05) showed that both variables significantly affected spin serve effectiveness (R² = 0.551; p < 0.05). Grip strength had a greater contribution (β = 0.46; p = 0.008) than motion anticipation (β = 0.39; p = 0.018). The findings highlight the importance of integrating physical and cognitive training to enhance spin serve performance in junior tennis athletes. Strength and anticipation training should be combined to optimize serve outcomes